Cross-front variations in adult abundance and recruitment of Patagonian scallop (Zygochlamys patagonica) at the SW Atlantic Shelf Break Front - Mauna, Andrea Cecilia (2008)
We studied cross-front variations in adult abundance and recruitment of Patagonian scallop ( Zygochlamys patagonica ) and their relationship with the Shelf Break Front and satellite-derived chlorophyll a in the Southwest Atlantic between 38 8 S and 39 8 30 0 S. Integrated data from commercial fleets (CF, 1996–2005), research cruises (RC, 1998–2005), sea surface temperature (SST; 1985– 1997), and satellite-derived chlorophyll a (CSAT; 1998–2004) were included in the analysis. One-way ANOVA was used to assess differ- ences in recruitment and scallop abundance in a cross-front direction. The abundance of scallops was greatest (RC . 200 kg h 2 1 ) closer to the onshore side of the front or beneath it, and the East–West extension of scallop beds ( 40 km) matched the seasonal zonal displacement of the front ( 37 km). The highest CSAT gradients were west of or matched the position of the front. The annual mean position of the front correlated with the spatial variability in recruitment within areas where the species recruited successfully (RC . 2000 h 2 1 ). The spatial variability in adult abundance and recruitment of scallops is strongly related to the spatial variability in the position of the front and with the high CSAT concentrations associated with it.